تقييم صيانة الآليات باعتماد مؤشرات الأداء الرئيسة - يوسف أيمن; المحمودي حاتم; علي تغريد (Latakia University Journal -Engineering Sciences Series, 2017)
يتضمن هذا البحث تقييم عمل صيانة الآليات من خلال مؤشرات الأداء الرئيسة الخاصة بها، والمعتمدة من قبل الشركات الصناعية والخدمية ونذكر منها الموثوقية، والجاهزية، متوسط الزمن بين الأعطال، متوسط زمن اصلاحالأعطال، متوسط زمن الصيانة الدورية لمعداتها الانتاجية والخدمية. بعد معالجة البيانات الخاصة بالأعطال الطارئة والصيانة الدورية التي تمت على الآليات تم استخلاص قيم المؤشرات الخاصة بالصيانة وقياس أداءها وترابطها لمعرفة مدى مطابقتها مع المؤشرات العالمية الموجودة. يهدف البحث إلى تقييم الوضع الراهن من خلال استخدام نمط الأساليب الكمية المستخدمة في الوصول لقيم مؤشرات الأداء السابقة الذكر وترابطها لاستخدامها في دعم قرارات الصيانة في محطة الحاويات لاحقاً. تم التوصل إلى ارتباط عكسي قوي بين زمن الصيانة الدورية TPM وزمن إصلاح الأعطال TBD ، وصلت قيمته rERS= -0.99، وبالتالي يجب التركيز على زيادة عمليات الصيانة الدورية للتقليل من زمن إصلاح الأعطال، وإجراء استبدال للأجزاء التي تسبب المشاكل المتكررة حيث تسببت بأعطال دورية مكثفة مما يقلل من زمن الصيانة الدورية. كما تمكنا من تصنيف جودة الصيانة والآلات من خلال مؤشرات الجاهزية والموثوقية ومتوسط الزمن بين الأعطال. This research includes evaluating the work of maintenance of themachines through their own key performance indicators (KPI), and approved byindustrial and service companies, We mention reliability, readiness, average time between failures, average Repair time, average time of periodic maintenance of their production and serviceequipment . After the data processing of emergency failures and periodic maintenanceof machines , we extracted values for maintenance performanceindicators, we measured their performance and correlation to evaluateits compatibility with global indicators. The research aim to assess the current situation through the use ofquantitative methods pattern which is used to access the values of theprevious mentioned performance indicators and their interdependence tobe used in support of maintenance decisionsin the container terminal later. We noticed a strong inverse association between periodic maintenance TPMtime and breakdown TBD, and reached a value rERS = -0.99, and thereforewe must focus on increasing periodic maintenance to reduce breakdowntime, and replace parts that cause recurringproblems which caused about intensive breakdowns, thus reducing periodicmaintenance time. Also we were able to classify the quality of maintenance and machinesthrough the readiness and reliability indicators and the mean timebetween failures.